Molecular Dynamics Simulations of a Cationic Thiophene Oligomer and a Nucleotide Complex - Elmacı Irmak, Nuran; Demirci, Fethi Can; Elmacı Irmak, Nuran (Izmir Institute of Technology, 2022)
In this thesis, parametrization of cationic polythiophene (CPT) and molecular dynamics (MD) simulations of CPT with DNA complexes were performed to understand the behaviors of the CPT with DNA complex and CPT DNA complexes in different salt solutions (NaCl, KCl, MgCl2, CaCl2). The results of MD simulations show that the end-to-end distance of CPT is affected by both the type sequences and length of the DNA, and the addition of 20T elongates the backbone of the oligomer while 20A and MIX ssDNAs almost have no significant effect. When the complementary DNA chain is added to the duplex solutions, the backbone structure of the oligomer becomes very similar to its structure without ssDNAs since Ree values in both cases are almost the same. It was observed that the CPT-20A complex has a more random coil form than the CPT-20T complex. According to the interaction analysis of MD simulations, all the CPT-DNA duplexes except CPT-20A prefer electrostatic interaction rather than π-cation interaction. DNAs like to interact with the oligomer's side chain rather than its backbone in all systems. Thus, electrostatic interactions and the side chain of oligomer play an important role in the structure of duplexes with thymine which gets the highest response from the oligomer. The addition of 20T makes backbone of F0 more elongated and less compact. 20T has higher electrostatic and π-cation interactions. Thus, F0 is more sensitive to 20T than 20A and MIX.

Bu tez çalışmasında, uzun yan zincirli bir katyonik politiyofen için simülasyon veri tabanlarında olmayan kuvvet alanı parametreleri elde edildi. Katyonik politiyofenin farklı ortamlarda (Tuzsuz, NaCl, KCl, MgCl2, CaCl2) DNA ile kompleksleşmesini anlamak amacıyla moleküler dinamik simülasyonlar gerçekleştirilmiştir. Yapılan analizlerin sonucuna göre, DNA’nın sekansı ve uzunluğu CPT’nin baş-son uzunluğunu (Ree) etkilemiştir. CPT yanına 20T ssDNA eklenmesi polimer omurgasını uzatırken 20A ve MIX ssDNAlarının hemen hemen hiç etkisi olmadığı gözlenmiştir. Dublekslerin üzerine tamamlayıcı DNA zinciri eklendiğinde ise oligomerin yapısının kompleksleşmeden önceki haline dönüştüğü izlendi (Ree’leri yaklaşık olarak aynı). CPT-20A kompleksi COPT-20T kompleksine göre daha büzülmüş bir yapıya sahip olduğu görülmüştür (Rg değerine göre). MD simülasyonları sonuçlarına yapılan etkileşim analizlerine göre, CPT-20A hariç tüm CPT-DNA kompleksleri π-katyona göre elektrostatik etkileşimleri tercih etmektedir. DNA’ların çoğunlukla oligomerin iskeleti yerine yan zinciriyle etkileşmeyi seçtikleri gözlenmiştir. 20T’nin eklenmesi F0’ın omurgasını uzatıp daha az kompakt bir hale getirmiştir. 20T’de polimer ile daha fazla π-katyon ve elektrostatik etkileşimlere sahiptir. Dolayısıyla, F0 20T’ye 20A ve MIX e göre daha duyarlıdır
Bir Katyonik Tiyofen Oligomeri ve Nükleotit Kompleksinin Moleküler Dinamik Benzetimleri
Thesis (Master)--Izmir Institute of Technology, Chemistry, Izmir, 2022
Includes bibliographical references (leaves. 31-34)
Text in English; Abstract: Turkish and English
Keywords: Moleculer dynamics simulations; Polythiophene; Cationic polythiophenes; Parametrization